2019
DOI: 10.1021/acs.chemmater.9b01209
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional Characterization of Mixed Ligand Nanoparticles Using Small Angle Neutron Scattering

Abstract: The properties of ligand protected gold nanoparticles are determined by the synergistic interplay of their structural components, including the metal core, the ligand shell, and its solvation. However, the simultaneous characterization of all these components remains a major challenge given their distinctly different chemical nature. In the case of mixed ligand nanoparticles, this task becomes daunting due to the presence of intercorrelated additional parameters such as the ligand ratio, ligand spatial distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 73 publications
(223 reference statements)
0
15
0
Order By: Relevance
“…Mass spectroscopy has been used to determine ligand ratios in the monolayer , and has also been shown to provide information on ligand phase separation . Other spectroscopic methods for the determination of monolayer ligand composition include XPS and TGA. ,, When specific types of molecules containing isotopes or free radicals are present in the monolayer, SANS and EPR can also be powerful tools for ligand chacterization. For nanoparticle films, electrical conductivity measurements can also be used for the ligand monolayer characterization of the films. Due to their sensitivity to interparticle separation, both the resistivity and the impedance of the films are sensitive to changes in the monolayer composition , and could be used to determine the ligand composition of the films.…”
Section: Characterization Of Mixed-ligand Monolayersmentioning
confidence: 99%
“…Mass spectroscopy has been used to determine ligand ratios in the monolayer , and has also been shown to provide information on ligand phase separation . Other spectroscopic methods for the determination of monolayer ligand composition include XPS and TGA. ,, When specific types of molecules containing isotopes or free radicals are present in the monolayer, SANS and EPR can also be powerful tools for ligand chacterization. For nanoparticle films, electrical conductivity measurements can also be used for the ligand monolayer characterization of the films. Due to their sensitivity to interparticle separation, both the resistivity and the impedance of the films are sensitive to changes in the monolayer composition , and could be used to determine the ligand composition of the films.…”
Section: Characterization Of Mixed-ligand Monolayersmentioning
confidence: 99%
“…Stellacci and coworkers showed that SANS could distinguish nanomaterials that differed only a few angstroms in their size or only a few molecules in their ligand shell. 72 Two ligands, 11mercaptoundecanoic acid (MUA) and 1-octanethiol (OT), were conjugated to AuNPs. Two different samples were prepared where only one ligand was deuterated: MUA-(OT-d) AuNP and (MUA-d)-OT AuNP.…”
Section: Brmentioning
confidence: 99%
“…Atomic emission spectroscopy (AES) may provide yield values with no a priori knowledge of the analysed nanoparticles. Furthermore, there is also a need for the development and implementation of techniques that offer in situ information of the ligand shell, such as small angle neutron scattering (SANS) [60] and quartz crystal microbalance with dissipation monitoring [61].…”
Section: Synthesis In Flow Reactorsmentioning
confidence: 99%